Proceedings of Patient Reported Outcome Measure's (PROMs) Conference Sheffield 2016: advances in patient reported outcomes research. Issue 1 (October 2016) - Croudace, Tim; Brazier, John; Gutacker, Nils; Street, Andrew; Robotham, Dan; Waterman, Samantha; Rose, Diana; Satkunanathan, Safarina; Wykes, Til; Nasr, Nasrin; Enderby, Pamela; Carlton, Jill; et al.
Table of contents S1 Using computerized adaptive testing Tim Croudace S2 Well-being: what is it, how does it compare to health and what are the implications of using it to inform health policy John Brazier O1 "Am I going to get better?"—Using PROMs to inform patients about the likely benefit of surgery Nils Gutacker, Andrew Street O2 Identifying Patient Reported Outcome Measures for an electronic Personal Health Record Dan Robotham, Samantha Waterman, Diana Rose, Safarina Satkunanathan, Til Wykes O3 Examining the change process over time qualitatively: transformative learning and response shift Nasrin Nasr, Pamela Enderby O4 Developing a PROM to evaluate self-management in diabetes (HASMID): giving patients a voice Jill Carlton, Donna Rowen, Jackie Elliott, John Brazier, Katherine Stevens, Hasan Basarir, Alex Labeit O5 Development of the Primary Care Outcomes Questionnaire (PCOQ) Mairead Murphy, Sandra Hollinghurst, Chris Salisbury O6 Developing the PKEX score- a multimodal assessment tool for patients with shoulder problems Dominic Marley, James Wilson, Amy Barrat, Bibhas Roy O7 Applying multiple imputation to multi-item patient reported outcome measures: advantages and disadvantages of imputing at the item, sub-scale or score level Ines Rombach, Órlaith Burke, Crispin Jenkinson, Alastair Gray, Oliver Rivero-Arias O8 Integrating Patient Reported Outcome Measures (PROMs) into routine primary care for patients with multimorbidity: a feasibility study Ian Porter, Jaheeda Gangannagaripalli, Charlotte Bramwell, Jose M. Valderas O9 eRAPID: electronic self-report and management of adverse-events for pelvic radiotherapy (RT) patients Patricia Holch, Susan Davidson, Jacki Routledge, Ann Henry, Kevin Franks, Alex Gilbert, Kate Absolom & Galina Velikova O10 Patient reported outcomes (PROMs) based recommendation in clinical guidance for the management of chronic conditions in the United Kingdom Ian Porter, Jose M.Valderas O11 Cross-sectional and longitudinal parameter shifts in epidemiological data: measurement invariance and response shifts in cohort and survey data describing the UK's Quality of Life Jan R. Boehnke O12 Patient-reported outcomes within health technology decision making: current status and implications for future policy Andrew Trigg, Ruth Howells O13 Can social care needs and well-being be explained by the EQ-5D? Analysis of Health Survey for England dataset Jeshika Singh, Subhash Pokhrel, Louise Longworth O14 Where patients and policy meet: exploring individual-level use of the Long-Term Conditions Questionnaire (LTCQ) Caroline Potter, Cheryl Hunter, Laura Kelly, Elizabeth Gibbons, Julian Forder, Angela Coulter, Ray Fitzpatrick, Michele Peters